Persistence in epidemic metapopulations: quantifying the rescue effects for measles, mumps, rubella and whooping cough. - C Jessica E Metcalf; Katie Hampson; Andrew J Tatem; Bryan T Grenfell; Ottar N Bjørnstad (PLoS ONE)
Metapopulation rescue effects are thought to be key to the persistence of many acute immunizing infections. Yet the enhancement of persistence through spatial coupling has not been previously quantified. Here we estimate the metapopulation rescue effects for four childhood infections using global WHO reported incidence data by comparing persistence on island countries vs all other countries, while controlling for key variables such as vaccine cover, birth rates and economic development. The relative risk of extinction on islands is significantly higher, and approximately double the risk of extinction in mainland countries. Furthermore, as may be expected, infections with longer infectious periods tend to have the strongest metapopulation rescue effects. Our results quantitate the notion that demography and local community size controls disease persistence.